Odd generalized exponential log logistic distribution: A new acceptance sampling plans based on percentiles - Srinivasa Rao Gadde; K. Rosaiah; D. C. U. Sivakumar; K. Kalyani (International Journal of Advances in Applied Sciences, 2019)
In this paper, acceptance sampling plans are developed for the odd generalized exponential log logistic distribution based on percentiles when the life test is truncated at a pre-specified (pre-determined) time. The minimum sample size necessary to ensure the specified life percentile is obtained under a given consumer’s risk. The operating characteristic values of the sampling plans as well as the producer’s risk are presented. One example with real data set is also given as an illustration.